High intensity organic pigments and methods for their preparation

CN122326016BActive Publication Date: 2026-10-09JIANGSU LYNWON TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610590869.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-30
Publication Date
2026-10-09
Estimated Expiration
2046-04-30

AI Technical Summary

Technical Problem

[0003]然而,这一发展方向遭遇了一个无法回避的核心固有矛盾:颜料颗粒极细化必然伴随表面能的急剧升高,导致在干燥、存储及后续应用分散过程中发生不可逆的严重二次团聚

Benefits of technology

1、本发明突破了传统高能耗机械研磨易导致颜料晶型破坏和局部碳化的技术瓶颈,采用樟脑与薄荷醇按特定比例形成的低共熔混合物作为固体分散介质,在深冷状态下形成具脆性的刚性磨介,不仅能高效传递极高剪切力,还将自身如“楔子”般嵌入颜料破裂产生的新生表面,实现低能耗下的纳米级剥离;研磨结束后,利用该介质易升华的特性,在温和真空下直接将其转变为气体抽离,避免了传统湿法研磨后液相溶剂挥发所产生的巨大毛细管收缩力,从源头切断了颜料颗粒在脱溶剂阶段发生硬团聚的可能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122326016B_ABST
    Figure CN122326016B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of organic pigments, in particular to a high color strength organic pigment and a preparation method thereof. The present application overcomes the problem that the color strength of organic pigments decreases due to secondary agglomeration after refinement. The crude organic pigment red 254 is mixed with a eutectic medium and subjected to cryogenic shearing to achieve extreme refinement, and then the medium is removed by vacuum sublimation. A coating agent with catechol groups and long-chain alkyl groups is prepared, and a modified two-dimensional layered double hydroxide barrier agent is prepared by formamide stripping. Through a Y-type microchannel reactor, high-intensity impinging streams are used to cause rapid phase change between good solvents and poor solvents, achieving in-situ self-assembly coating of nano pigments. Finally, water-alcohol constant ratio replacement is used in combination with microwave radiation for rapid distillation drying from the inside out, and the prepared organic pigment has no hard agglomeration, has a loose porous structure, and has excellent dispersion in the application system, and the color strength is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic pigment technology, specifically to a high-intensity organic pigment and its preparation method. Background Technology

[0002] Organic pigments are widely used in inks, coatings, plastics, and textile printing. Color intensity is one of the most important application indicators for organic pigments, directly determining their coloring ability and economic value in a substrate. According to optical scattering theory, the color intensity of organic pigments is closely related to the particle size of their primary particles: within a certain range, the smaller the particle size and the larger the specific surface area, the stronger their ability to absorb and scatter light, and the higher the color intensity. Therefore, traditional process improvements often focus on refining pigment particles to the nanoscale through methods such as intense grinding and acid-soluble phase transfer.

[0003] However, this development direction encounters an unavoidable core inherent contradiction: the extreme fineness of pigment particles inevitably leads to a sharp increase in surface energy, resulting in irreversible and severe secondary agglomeration during drying, storage, and subsequent application dispersion. This strong agglomeration effect not only prevents the theoretically high color intensity from being realized in practical applications but also leads to uneven pigment distribution in the substrate, dull color, and reduced gloss. Existing solutions mainly focus on two directions: one is relying on long-term high-energy mechanical grinding, but this is prone to local overheating, crystal transformation, and even pigment carbonization; the other is using traditional surfactant adsorption and coating, but these weak physical adsorption layers are easily detached under capillary contraction forces generated by solvent evaporation or high-shear application environments, failing to provide permanent spatial isolation. Therefore, how to break the inherent contradiction between "extreme fineness and high agglomeration," and simultaneously achieve crystal micronization while locking the primary particle morphology through a permanent physical / chemical synergistic barrier, has become a bottleneck problem that urgently needs to be solved in this field.

[0004] To address this, a high-intensity organic pigment and its preparation method are proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a high-intensity organic pigment and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: Unless otherwise specified, all parts in this invention are parts by weight.

[0007] This invention provides a method for preparing a high-intensity organic pigment, the method being as follows: 100 parts of refined pigment powder and 8 parts of coating agent are dispersed in 800 parts of anhydrous N,N-dimethylformamide to obtain solution A; 5 parts of modified barrier agent are dispersed in a mixture of 1000 parts of deionized water and 150-250 parts of n-butanol, and the pH value is adjusted to 8 using 5wt% ammonia water to obtain solution B; solutions A and B are subjected to in-situ coating to obtain a pigment suspension; the pigment suspension is subjected to microwave-assisted azeotropic distillation to obtain a high-intensity organic pigment. The coating agent is prepared by reacting caffeic acid and hexadecylamine; The modified barrier agent is prepared by reacting magnesium aluminum layered double hydroxide, formamide and sodium oleate.

[0008] The preferred method for preparing refined pigment powder is as follows: Camphor and menthol are mixed in a molar ratio of 1:1, heated to 45°C and stirred for 15 minutes to obtain a eutectic medium; 100 parts of crude organic pigment Red 254 (item number S68370, purchased from Shanghai Yuanye Biotechnology Co., Ltd.) are mixed evenly with 300 parts of the eutectic medium and put into a high-shear mill equipped with a cooling jacket. Liquid nitrogen is introduced to cool the temperature to -30°C to -50°C. After the material is completely embrittled and solidified, the mill speed is set to 1200 rpm and the grinding treatment is carried out for 1-2.5 hours. Then, the material is transferred to a vacuum condensation drying oven and treated at a temperature of 35°C and a vacuum degree of 50 Pa for 3-5 hours to allow the camphor and menthol to completely sublimate and be collected to obtain refined pigment powder.

[0009] Preferably, the coating agent is prepared as follows: 100 parts of anhydrous N,N-dimethylformamide are ultrasonically degassed and continuously bubbled with high-purity nitrogen for 30 minutes to remove dissolved oxygen; under nitrogen protection, 15-20 parts of caffeic acid and 0.1 parts of ascorbic acid are dissolved in the above solvent; 5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 3 parts of N-hydroxysuccinimide are added as coupling catalysts, and the mixture is stirred and activated for 1.5 hours; subsequently, under ice-water bath cooling, 100 parts of deoxygenated anhydrous N,N-dimethylformamide containing 20-28 parts of hexadecylamine is added dropwise. After the addition was complete, the ice bath was removed, and the reaction was carried out at room temperature and 300 rpm for 12 hours. After the reaction was completed, the reaction mixture was slowly added dropwise to 900 parts of ice-cold deionized water with a stirring speed of 800 rpm. At this time, the target product precipitated out in large quantities due to the sudden change in polarity, while the solvent N,N-dimethylformamide and water-soluble byproducts remained in the aqueous phase. After stirring for another 30 minutes, the mixture was filtered and the filter cake was washed three times with deionized water until neutral. Finally, the filter cake was placed in a vacuum drying oven and dried at 50℃ and -0.09 MPa for 12 hours to obtain the coating agent.

[0010] The solvent was removed by rotary evaporation under reduced pressure, and the product was washed with deionized water and dried at 50°C and a vacuum of -0.09 MPa for 12 hours to obtain the coating agent.

[0011] Preferably, the modified barrier agent is prepared as follows: 8-12 parts of magnesium-aluminum layered double hydroxide are added to 200 parts of formamide. The mixture is mechanically stirred at 150 rpm at room temperature and treated with ultrasound (300 W power, 28 kHz frequency) for 24 h to completely exfoliate it into a translucent single-layer nanosheet colloidal solution. 80 parts of n-butanol are added to the system as a transition solvent, and then 20 parts of ethanol solution containing 1.5-3 parts of sodium oleate are added dropwise. The temperature is raised to 50-70℃, and the mixture is stirred at 400 rpm for 4 h to perform surface modification. After the reaction, 400 parts of deionized water are added to the system to break the solvent polarity balance, causing the modified nanosheets to precipitate in a loose flocculated state. The bottom wet gel product is collected by centrifugation (2000 rpm). The wet gel product is directly added to 100 parts of n-butanol and treated with ultrasound at 200 W, 40 kHz for 30 min to perform in-situ rapid swelling and resuspension, thus obtaining the modified barrier agent.

[0012] The product was collected by centrifugation, washed twice with anhydrous ethanol, and redispersed in n-butanol for later use to obtain the modified barrier agent.

[0013] Preferably, the pigment suspension preparation method is as follows: Liquid A and liquid B are injected into a Y-type microchannel reactor (channel inner diameter 700 μm, jacket temperature maintained at 45℃) at flow rates of 20-30 mL / min and 80-100 mL / min respectively using a dual-plunger pump. The high flow rate of liquid B forms high-speed shear and scouring of liquid A. The two fluids undergo a millisecond-level phase transition at the intersection of the microchannel, generating a fully coated pigment suspension in situ, which is then quickly carried out by the fluid, avoiding local accumulation and blockage of high solid content.

[0014] Preferably, the microwave-assisted azeotropic step is as follows: the pigment suspension is filtered, and the filter cake is washed with deionized water to remove N,N-dimethylformamide; a mixed solvent of deionized water and n-butanol with a mass ratio of 50:50-60:40 is prepared in advance, and the filter cake is resuspended, washed, and filtered three times using this mixed solvent. The liquid phase inside the filter cake is completely replaced with a constant ratio mixed solvent of 50:50-60:40 by using concentration equilibrium; the wet filter cake obtained from the last washing is transferred into a microwave vacuum drying reactor for constant ratio azeotropic drying. The microwave power is set to 600-1000W, and the system vacuum degree is -0.08MPa. Under microwave radiation, the system boils at about 65°C, and the water-n-butanol azeotrope is rapidly evaporated from the inside out. Drying is continued for 1.5 hours until no condensate drips out, resulting in a high-intensity organic pigment.

[0015] Another aspect of the present invention provides a high-color-strength organic pigment, which is prepared by any of the above-described preparation methods; the raw materials for preparing the high-color-strength organic pigment include refined pigment powder, coating agent and modified barrier agent.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention breaks through the technical bottleneck of traditional high-energy mechanical grinding, which easily leads to pigment crystal destruction and local carbonization. It uses a eutectic mixture of camphor and menthol in a specific ratio as a solid dispersion medium. Under deep cryogenic conditions, it forms a brittle rigid grinding medium that can not only efficiently transmit extremely high shear force, but also embed itself like a "wedge" into the newly formed surface of the pigment fracture, achieving nanoscale exfoliation with low energy consumption. After grinding, taking advantage of the sublimation property of this medium, it is directly converted into gas and extracted under a mild vacuum. This avoids the huge capillary contraction force generated by the evaporation of liquid solvent after traditional wet grinding, and cuts off the possibility of hard agglomeration of pigment particles in the desolventization stage from the source.

[0017] 2. This invention prepares a coating agent. One end of the modified molecule is rich in catechol groups, which can spontaneously perform high-strength cross-linking and anchoring at multiple sites on the pigment surface. Its binding force far exceeds the weak physical adsorption of conventional surfactants, ensuring that it does not fall off in subsequent high-shear application environments. The long-chain alkyl groups grafted to the other end extend outward to form a steric hindrance layer. This dual-effect mechanism of "strong gripping-peripheral repulsion" constructs a dense and elastic steric hindrance layer around the pigment particles, effectively offsetting the extremely high surface energy of the nanoparticles and giving the product excellent dispersion stability.

[0018] 3. To address the limitation of traditional inorganic coated particles (such as spherical silica) which can only provide point-contact isolation, this invention employs a magnesium-aluminum layered double hydroxide. First, formamide is used to completely exfoliate it into a single-layer two-dimensional nanosheet, and then sodium oleate is used to hydrophobically modify its surface. Through the synergy of physical exfoliation and chemical modification, these extremely thin two-dimensional flexible "nanoblanets" with a very high aspect ratio can tightly adhere to and wrap around the outside of pigment particles in a surface-contact manner, maximizing the isolation of the strong van der Waals association and π-π conjugation stacking effect between adjacent organic pigment molecules, thus ensuring the maximum manifestation of the optical scattering efficiency of nanoscale pigment particles.

[0019] 4. This invention overcomes the shortcomings of traditional stirred coating methods in reaction vessels, such as large concentration gradients and uneven coating, by innovatively introducing microchannel continuous impingement flow technology. A benign solvent carrying pigment particles is mixed with a poor solvent containing a barrier agent at extremely high speeds. Due to the extremely high Reynolds number within the micron-scale channels, mixing is completed within milliseconds, achieving extremely uniform nanoscale explosive nucleation of the pigment. Simultaneously, at the instant of primary nanoparticle generation, the coating agent and two-dimensional nanosheets self-assemble in situ under hydrodynamic forced compression, achieving a synergistic mechanism of "protection from birth."

[0020] 5. In the final dehydration and shaping stage, this invention uses a water-alcohol constant ratio solvent washing and replacement method to eliminate interference from high-boiling-point solvents, and applies a microwave radiation field. Microwave radiation can selectively heat the highly polar pigment-water interface, causing the azeotrope to vaporize from the inside of the particles to the outside. This "inside-out" airflow not only instantly removes moisture, but also fully expands and shapes the hydrophobic long chains wrapped on the pigment surface, completely avoiding the densification defects caused by the shrinkage from the outside to the inside in traditional hot air drying. This results in the final pigment powder exhibiting an extremely loose and porous state and excellent secondary dispersion performance. Attached Figure Description

[0021] Figure 1 The graph shows the test results of relative tinting strength and fixation rate of the reference standard and Examples 1-4 of this invention. Detailed Implementation

[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] Please see Figure 1 This invention provides a high-intensity organic pigment and its preparation method, the technical solution of which is as follows: Example 1

[0024] 100 parts of anhydrous N,N-dimethylformamide were ultrasonically degassed and continuously bubbled with high-purity nitrogen for 30 minutes to remove dissolved oxygen. Under nitrogen protection, 15 parts of caffeic acid and 0.1 parts of ascorbic acid were dissolved in the above solvent. 5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 3 parts of N-hydroxysuccinimide were added as coupling catalysts, and the mixture was stirred and activated for 1.5 hours. Subsequently, under ice-water bath cooling, 100 parts of deoxygenated N,N-dimethylformamide containing 20 parts of hexadecylamine was added dropwise. Anhydrous N,N-dimethylformamide was added dropwise, and the ice bath was removed after the addition was complete. The mixture was then reacted at room temperature and 300 rpm for 12 hours. After the reaction was completed, the reaction mixture was added dropwise to 900 parts of ice-cold deionized water at a stirring speed of 800 rpm. The mixture was stirred for another 30 minutes and then filtered. The filter cake was washed three times with deionized water until neutral. Finally, the filter cake was placed in a vacuum drying oven and dried at 50°C and -0.09 MPa for 12 hours to obtain the coating agent.

[0025] 15 parts of caffeic acid were dissolved in 100 parts of anhydrous N,N-dimethylformamide. Under light-protected and nitrogen-protected conditions, 5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 3 parts of N-hydroxysuccinimide were added as coupling catalysts, and the mixture was stirred and activated for 1.5 h. 100 parts of anhydrous N,N-dimethylformamide containing 20 parts of hexadecylamine were added dropwise. After the addition was complete, the temperature was raised to 40 °C and the reaction was carried out at 300 rpm for 12 h. After the reaction was completed, the reaction mixture was added dropwise to 900 parts of ice-cold deionized water with a stirring speed of 800 rpm. After stirring for 30 min, the mixture was filtered and the filter cake was washed three times with deionized water until neutral. Finally, the filter cake was placed in a vacuum drying oven and dried at 50 °C and -0.09 MPa for 12 h to obtain the coating agent.

[0026] 51.3 parts of Mg(NO3)2·6H2O and 37.5 parts of Al(NO3)3·9H2O were added to 200 parts of deionized water and stirred at 300 rpm for 30 min at room temperature to obtain a clear and transparent mixed metal salt solution. 20 parts of sodium hydroxide and 10.6 parts of anhydrous sodium carbonate were dissolved in 150 parts of deionized water and stirred until homogeneous to obtain a mixed alkali solution. 50 parts of deionized water were pre-added to the reaction vessel as a base solution and heated to 40°C, then stirred at 600 rpm. Subsequently, the mixed metal salt solution and the mixed alkali solution were simultaneously added dropwise to the reaction vessel using a dual-channel micro-titration pump, controlling the drop rate of the salt solution at 2 mL / min. Simultaneously, the mixed alkali solution was dynamically adjusted. The dropping rate was adjusted to maintain the pH of the reaction system at 10.0 ± 0.2 throughout the process. After the addition was complete, stirring was continued at 40°C for 1 hour to obtain a white suspension. The white suspension was transferred to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner and sealed. It was placed in a homogeneous reaction chamber and heated to 80°C at a rate of 2°C / min for 24 hours to crystallize. After crystallization, the reactor was allowed to cool naturally to room temperature. The product was centrifuged at 8000 rpm for 10 minutes. The filter cake was washed three times with alternating resuspension using deionized water and anhydrous ethanol until the washing liquid was neutral. Finally, it was dried at 60°C under vacuum of -0.08 MPa for 12 hours. Eight portions of magnesium-aluminum layered double hydroxide (Mg-Al) were taken. LDH was added to 200 parts of formamide, and the mixture was mechanically stirred at 150 rpm at room temperature and treated with ultrasound (300 W, 28 kHz) for 24 h. 80 parts of n-butanol were added to the system, followed by dropwise addition of 20 parts of ethanol solution containing 1.5 parts of sodium oleate. The mixture was heated to 50 °C and stirred at 400 rpm for 4 h for surface modification. After the reaction was completed, 400 parts of deionized water were added to the system. The bottom wet gel product was collected by centrifugation (2000 rpm). The wet gel product was directly added to 100 parts of n-butanol and treated with ultrasound at 200 W, 40 kHz for 30 min to obtain the modified barrier agent.

[0027] Camphor and menthol were mixed in a molar ratio of 1:1 and heated to 45°C and stirred for 15 minutes to obtain a eutectic medium. 100 parts of crude organic pigment Red 254 and 300 parts of the eutectic medium were mixed evenly and put into a high-shear mill equipped with a cooling jacket. Liquid nitrogen was introduced to cool the mill to -30°C. After the material was completely embrittled and solidified, the mill speed was set to 1200 rpm and the milling process was carried out for 1 hour. After that, the mill was transferred to a vacuum condensation drying oven and treated at 35°C and 50 Pa for 3 hours to allow the camphor and menthol to completely sublimate and be collected, resulting in refined pigment powder.

[0028] 100 parts of refined pigment powder and 8 parts of coating agent were dispersed in 800 parts of anhydrous N,N-dimethylformamide to obtain solution A; 5 parts of modified barrier agent were dispersed in a mixture of 1000 parts of deionized water and 150 parts of n-butanol, and the pH was adjusted to 8 with 5 wt% ammonia to obtain solution B; solutions A and B were pumped at 20 mL / min and 80 mL / min respectively using a dual-plunger pump. The fluid is injected into a Y-type microchannel reactor (channel inner diameter 700 μm, jacket temperature maintained at 45 °C) at a flow rate of mL / min. The two fluids undergo millisecond-level high-intensity collisions and rapid phase transitions at the confluence of the microchannels, generating a fully coated pigment suspension in situ. The pigment suspension is then filtered, and the filter cake is washed with deionized water to remove N,N-dimethylformamide. A 50:50 mass ratio of deionized water to n-butanol is prepared in advance. The filter cake is then resuspended, washed, and filtered three times using this mixed solvent. Concentration equilibrium is used to completely replace the liquid phase inside the filter cake with a constant 50:50 mixed solvent. The wet filter cake obtained from the last washing is transferred to a microwave vacuum drying reactor for constant-ratio azeotropic drying. The microwave power is set to 600 W, the system vacuum degree is -0.08 MPa, and drying is continued for 1.5 h until no condensate drips out, yielding a high-intensity organic pigment.

[0029] Example 2

[0030] The preparation method and parameters were the same as in Example 1, except that when preparing the coating agent, the amount of caffeic acid was 17 parts and the amount of hexadecylamine was 23 parts; when preparing the modified barrier agent, 9 parts of Mg-Al LDH were exfoliated in 200 parts of formamide, and 20 parts of ethanol solution containing 2 parts of sodium oleate were added, and the reaction was carried out at 60°C for 4 hours; when preparing the refined pigment powder, it was ground at -40°C for 1.5 hours and then sublimated under vacuum at 35°C for 4 hours; during in-situ coating and drying, the flow rate of solution A was 25 mL / min, and the flow rate of solution B was 85 mL / min (solution B contained 180 parts of n-butanol); the mass ratio of deionized water to n-butanol was 55:45, and the product was dried using microwave at 800W.

[0031] Example 3

[0032] The preparation method and parameters were the same as in Example 1, except that when preparing the coating agent, the amount of caffeic acid was 18 parts and the amount of hexadecylamine was 25 parts; when preparing the modified barrier agent, 10 parts of Mg-Al LDH were exfoliated in 200 parts of formamide, and 20 parts of ethanol solution containing 2.5 parts of sodium oleate were added, and the reaction was carried out at 65°C for 4 hours; when preparing the refined pigment powder, it was ground at -45°C for 2 hours and then sublimated under vacuum at 35°C for 4.5 hours; during in-situ coating and drying, the flow rate of solution A was 25 mL / min, and the flow rate of solution B was 90 mL / min (solution B contained 200 parts of n-butanol); the mass ratio of deionized water to n-butanol was 58:42, and the product was dried using a microwave at 900W.

[0033] Example 4

[0034] The preparation method and parameters were the same as in Example 1, except that when preparing the coating agent, the amount of caffeic acid was 20 parts and the amount of hexadecylamine was 28 parts; when preparing the modified barrier agent, 12 parts of Mg-Al LDH were exfoliated in 200 parts of formamide, and 20 parts of ethanol solution containing 3 parts of sodium oleate were added, and the reaction was carried out at 70°C for 4 hours; when preparing the refined pigment powder, it was ground at -50°C for 2.5 hours and then sublimated under vacuum at 35°C for 5 hours; during in-situ coating and drying, the flow rate of solution A was 30 mL / min, and the flow rate of solution B was 100 mL / min (solution B contained 250 parts of n-butanol); the mass ratio of deionized water to n-butanol was 60:40, and the product was dried using a microwave at 1000W.

[0035] Comparative Example 1 Following the preparation method and parameters of Example 1, except that the camphor and menthol eutectic medium was omitted, the crude organic pigment Red 254 was directly subjected to conventional wet high-shear milling at room temperature for 1.5 h (1200 rpm), and then vacuum dried at 60 °C and -0.09 MPa for 12 h.

[0036] Comparative Example 2 The preparation method and parameters of Example 1 were followed, except that the cryogenic grinding of the eutectic material was retained, but vacuum sublimation was not used to remove the medium. Instead, the ground material was added to 1000 parts of anhydrous ethanol and stirred and washed at 500 rpm for 30 min to dissolve camphor and menthol. Then, it was centrifuged at 8000 rpm for 10 min, and this washing was repeated 3 times. Finally, the filter cake was placed in a vacuum drying oven and dried at 60°C and a vacuum of -0.09 MPa for 12 h.

[0037] Comparative Example 3 The preparation method and parameters of Example 1 are the same, except that the self-made catechin-long-chain alkyl coating agent is not added in the preparation of solution A, and the refined pigment powder is directly dispersed in anhydrous N,N-dimethylformamide.

[0038] Comparative Example 4 The preparation method and parameters of Example 1 are the same, except that an equal amount of hexadecylamine is used to directly replace the "coating agent prepared by coupling reaction of caffeic acid and hexadecylamine", while the other steps remain unchanged.

[0039] Comparative Example 5 The preparation method and parameters of Example 1 are the same, except that no modified barrier agent is added in the preparation of solution B, and only a mixture of deionized water and n-butanol is used for subsequent phase change coating.

[0040] Comparative Example 6 The preparation method and parameters of Example 1 are the same, except that the barrier agent added to solution B is a magnesium-aluminum layered double hydroxide that has not been ultrasonically exfoliated with formamide and has not been hydrophobically modified with sodium oleate.

[0041] Comparative Example 7 The preparation method and parameters of Example 1 are the same, except that the Y-type microchannel reactor is not used and the traditional reaction vessel operation is used instead: liquid A is loaded into a dropping funnel, the dropping rate is controlled at 5 mL / min, and it is added dropwise to the reaction vessel containing liquid B. The mixture is stirred at 500 rpm for 2 hours to complete the precipitation.

[0042] Comparative Example 8 The preparation method and parameters of Example 1 were used, except that constant ratio displacement and microwave azeotropic treatment were not performed. The suspension was washed with water and then directly dried in an 80°C hot air oven.

[0043] Comparative Example 9 The preparation method and parameters of Example 1 were used, except that n-butanol in solution B and washing solution were omitted, and microwave vacuum drying was performed in a pure water system.

[0044] Experimental Example 1: Pigment Performance Testing Average particle size D 50 The determination was performed using dynamic light scattering (DLS). 0.1 g of pigment powder was added to 50 mL of anhydrous ethanol, ultrasonically dispersed for 5 min, and then sampled for testing. Relative tinting strength: Referring to the national standard GB / T 5211.19-1988 "Determination of relative tinting strength and diluted color of coloring pigments", 0.1g of the pigment sample to be tested was mixed with 1.0g of standard titanium dioxide (rutile type), and added to 1.2g of standard alkyd resin ink oil. The mixture was ground three times at 100 rpm with a force of 1kN on a grinder. The mixture was then evenly coated onto a standard black and white test card using a 100μm wire bar coater. After natural drying, the reflectance was measured using a spectrophotometer and the tinting strength was calculated. Unmodified crude organic pigment Red 254 was used as the reference standard (set to 100%). The higher the value, the stronger the tinting strength.

[0045] Centrifugal sedimentation rate: Disperse 5g of pigment in 95g of acrylic varnish at high speed for 30min; transfer to a stoppered graduated cylinder and centrifuge at 3000rpm for 30min, and measure the percentage of bottom sediment in total volume; Fixation rate: Referring to the industry standard for solvent resistance of paint film, the above-mentioned colored varnish was applied to a tinplate. After complete curing, it was immersed in methyl ethyl ketone (MEK) solvent for 24 hours, taken out and dried. The color difference before and after immersion was measured using a colorimeter and the tinting strength retention rate (i.e., fixation rate) was calculated. The results are shown in Table 1.

[0046] Table 1. Pigment performance tests of Examples 1-4 and Comparative Examples 1-9 Reference Standard 380 100 11.5 80.5 Example 1 75 141 1.1 96.5 Example 2 68 148 0.8 97.3 Example 3 60 156 0.4 98.2 Example 4 63 151 0.6 97.7 Comparative Example 1 185 112 4.6 85.2 Comparative Example 2 142 118 3.8 87.5 Comparative Example 3 125 115 5.4 82.1 Comparative Example 4 100 124 3.1 88.6 Comparative Example 5 88 131 2.5 90.4 Comparative Example 6 105 122 3.6 89.2 Comparative Example 7 81 135 1.9 92.5 Comparative Example 8 160 110 4.8 84.6 Comparative Example 9 75 134 1.6 94.0 As shown in Table 1, in Comparative Example 1, without the assistance of a cryogenically cured eutectic medium, simple wet milling could not generate sufficient "solid-phase wedging" shear force to break the strong intermolecular hydrogen bonds, resulting in the pigment not being sufficiently finely refined. Simultaneously, residual moisture caused significant capillary contraction during vacuum drying, leading to some hard agglomeration and a direct decrease in relative tinting strength. In Comparative Example 2, replacing the vacuum sublimation removal medium with anhydrous ethanol as the elution medium, although cryogenic refinement was achieved initially, the pigment particles were re-exposed to a liquid environment with surface tension when using liquid ethanol to wash the solid medium. During the subsequent vacuum drying process, the capillary contraction force generated by ethanol evaporation pulled the originally dispersed ultrafine nanoparticles together, forming irreversible secondary agglomeration, which negated the improvement in tinting strength brought about by pulverization. In Comparative Example 3, lacking the protection of the catechol-long-chain alkyl coating agent, the ultra-finely refined nano-pigments, in a state of ultra-high surface energy, spontaneously flocculated in the suspension. Due to the absence of any steric hindrance, particles directly collided and bonded, leading to an increased sedimentation rate. Simultaneously, pigment migration within the substrate was highly likely, resulting in a sharp drop in fixation rate. In Comparative Example 4, ordinary hexadecylamine, lacking catechol groups, could only remain on the pigment surface through very weak physical adsorption, failing to form strong covalent and coordination anchoring. During high-speed dispersion and polar solvent immersion tests, this weakly bound protective layer largely desorbed and became free, leading to steric hindrance failure, pigment re-flocculation, and poor sedimentation and fixation rates. In Comparative Example 5, the lack of physical encapsulation by the two-dimensional layered double hydroxide means that the steric hindrance of the long polymer chains alone cannot provide sufficient rigid isolation. When the pigment is drying or subjected to high shear stress, the cores of adjacent particles still have the opportunity to partially contact each other and generate π-π conjugated stacking associations, resulting in a slight increase in average particle size and limiting the complete release of extremely high tinting strength. In Comparative Example 6, the magnesium-aluminum layered double hydroxide, which has not been exfoliated with formamide and has not been hydrophobically modified, is a thick, multi-layered block. It not only fails to uniformly adhere to and encapsulate the pigment surface in a two-dimensional layered, flexible surface contact manner, but also becomes a new aggregation center in the organic system due to its own high polarity. This not only fails to provide a barrier effect, but also disrupts the rheological properties of the system, leading to a decrease in tinting strength. In Comparative Example 7, abandoning microfluidics and using traditional reactor dropwise addition resulted in macroscopic concentration gradients and mixing lag within the system. Nucleation and coating could not be completed simultaneously within milliseconds, causing some pigment particles to locally agglomerate before being coated (creating coating blind zones). This microscopic inhomogeneity broadened the product particle size distribution, preventing the overall color intensity and fixation rate from achieving the expected optimal results. In Comparative Example 8, traditional hot air drying is an outside-to-inside heating and mass transfer process. The strong capillary tension generated during moisture evaporation not only tightly compacted the particles but also severely compressed the originally extended alkyl chains. This "hard agglomeration" not only caused D... 50As the concentration increases, the powder becomes denser, making it extremely difficult to disperse again in the application system, resulting in a significant reduction in coloring power. In Comparative Example 9, the system lacks n-butanol, making it impossible to form a water-alcohol azeotrope. When water alone boils and vaporizes under microwaves, its high surface tension still exerts a certain degree of centripetal contraction force on the pigment particles. Furthermore, the lack of n-butanol's "swelling and stretching" effect on the hydrophobic long chains of the coating agent results in a final powder that is less porous than in the examples, with slightly elastic particle size and a slight decrease in performance.

[0047] From Table 1 and Figure 1 It can be seen that the present invention solves the inherent contradiction between "ultra-fine particle size and high agglomeration" of organic pigments not by simply piling up a single technology, but by constructing a multi-dimensional closed-loop anti-agglomeration technology route of "physical exfoliation - coating agent anchoring - two-dimensional rigid barrier - hydrodynamic self-assembly - phase lock-in shaping". Without the sublimation of the eutectic medium, the ultra-fine particle size process itself will induce agglomeration. And simply relying on traditional surface treatment or unexfoliated inorganic materials cannot resist the extremely high surface energy and π-π stacking association of nanoscale pigments. In addition, even if the material basis is complete, if the tension elimination mechanism from the inside out by microchannel instantaneous mixing and microwave azeotropic distillation is not achieved, all the previous ultra-fine particle size treatments will be in vain during the drying and shaping stage. Among them, the pigment prepared in Example 3 has the best comprehensive performance. In Example 4, due to the excessive amount of coating agent and the microwave power reaching 1000W, the coating layer thickness increased and slight thermal agglomeration occurred locally, resulting in a slight increase in the average particle size compared with Example 3.

[0048] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-intensity organic pigment, characterized in that: The preparation method is as follows: Refined pigment powder and a coating agent are dispersed in anhydrous N,N-dimethylformamide to obtain solution A; a modified barrier agent is dispersed in a mixture of deionized water and n-butanol, and the pH value is adjusted using ammonia to obtain solution B; solution A and solution B are subjected to in-situ coating to obtain a pigment suspension; the pigment suspension is subjected to microwave-assisted azeotropic distillation to obtain the high-intensity organic pigment. The coating agent is prepared by reacting caffeic acid and hexadecylamine; The modified barrier agent is prepared by reacting magnesium aluminum layered double hydroxide, formamide and sodium oleate; The method for preparing the refined pigment powder is as follows: Camphor and menthol are mixed and heated and stirred to obtain a eutectic medium; crude organic pigment Red 254 is mixed evenly with the eutectic medium and put into a high-shear grinding mill equipped with a cooling jacket. Liquid nitrogen is introduced to cool the temperature to -30°C to -50°C. After the material becomes brittle and solidified, it is ground for 1-2.5 hours and then transferred to a vacuum condensation drying oven for 3-5 hours to obtain the refined pigment powder. The coating agent is prepared as follows: under nitrogen protection, caffeic acid and ascorbic acid are dissolved in anhydrous N,N-dimethylformamide; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are added and stirred for activation; anhydrous N,N-dimethylformamide containing hexadecylamine is added dropwise, and the reaction is carried out at room temperature; after the reaction is completed, the coating agent is obtained by antisolvent precipitation. The modified barrier agent is prepared as follows: the magnesium-aluminum layered double hydroxide is added to the formamide, and mechanically stirred and ultrasonically treated at room temperature; the n-butanol and an ethanol solution containing the sodium oleate are added to it, and the temperature is raised to 50-70℃ and stirred to react; after the reaction is completed, a wet gel transfer is performed to obtain the modified barrier agent.

2. The method for preparing a high-intensity organic pigment according to claim 1, characterized in that: The pigment suspension is prepared as follows: liquid A and liquid B are injected into a Y-type microchannel reactor at flow rates of 20-30 mL / min and 80-100 mL / min, respectively, using a dual-plunger pump to generate a fully coated pigment suspension in situ.

3. The method for preparing a high-intensity organic pigment according to claim 1, characterized in that: The microwave-assisted azeotropic step is as follows: the pigment suspension is filtered and washed, a mixed solvent of deionized water and n-butanol in a mass ratio of 50:50-60:40 is prepared, the filter cake is resuspended, washed and filtered using the mixed solvent, and then transferred to a microwave vacuum drying reactor for drying. The microwave power is set to 600-1000W to obtain the high color intensity organic pigment.

4. A high-intensity organic pigment, characterized in that: The high-intensity organic pigment is prepared by the preparation method according to any one of claims 1-3; the raw materials for preparing the high-intensity organic pigment include refined pigment powder, coating agent and modified barrier agent.

Citation Information

Patent Citations

  • Hydrophobic halloysite based catechol chemical modification and preparation method of hydrophobic halloysite

    CN107955418A

  • Colored aluminum pigment capable of being directly used for injection molding and preparation method thereof

    CN109762374A